"I get a whiz in my body as I walk past it": Visceral imaginaries in children's everyday mobilities. (November 2022) - Joelsson, Tanja
Abstract: This article focuses on how the visceral, sensual and the imagined shape children's everyday mobility experiences and their meaning making around their everyday mobility, thus contributing to the growing field of study on children's emotional geographies and to the field of visceral geographies. By introducing the concept of visceral imaginaries, the role of the imagined in children's spatial and mobile experiences is highlighted and developed. The children further emerge as aged bodies in these visceral processes, as the affective practices and visceral imaginaries position children as aged subjects. The findings are based on a qualitative research project on children's practices and experiences of their everyday mobilities, in which 59 children (7–13 years old) participated, predominantly from white urban middle-class families in a mid-sized municipality in Sweden. Highlights: The visceral, sensual and the imagined shape children's everyday mobility experiences The concept of visceral imaginaries highlights the role of the imagined in children's mobile experiences. Children's affective practices and visceral imaginaries position children as aged bodies and aged subjects.